DOI: 10.11606/t.10.2018.tde-15082018-151229
|View full text |Cite
|
Sign up to set email alerts
|

<b>Avaliação de matrizes descelularizadas para regeneração muscular</b>

Abstract: Agradeço a Deus Pai Todo-poderoso por sempre ter estado ao meu lado e pela oportunidade que Ele me deu de estar aqui, hoje, concluindo mais uma etapa de minha vida. Etapa árdua, mas que com muita perserverança eu consegui chegar até o final. Agradeço eternamente a Virgem Maria pela Sua proteção e intercessão perante a Deus. "Eu sei que é difícil esperar, mas Deus tem um tempo para agir e para curar. Só é preciso confiar!!". Aos meus tios Nonato, Pedrinho, Ismael, Manoel e Zeca e, especialmente; às minhas marav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The above results showed that the polysaccharides extracted with 1 M NaOH at 20°C (FI) from wail material of G. ciride differed from those extracted from other penicillate fungi. They also correspond to previous results [1][2][3][4] in which the differences among several fungi v, ere found in this fraction.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…The above results showed that the polysaccharides extracted with 1 M NaOH at 20°C (FI) from wail material of G. ciride differed from those extracted from other penicillate fungi. They also correspond to previous results [1][2][3][4] in which the differences among several fungi v, ere found in this fraction.…”
supporting
confidence: 92%
“…2) showed an aborption band at 890 era-t characteristic of fl-linked polysaccharides. Periodate oxidation yielded glycerol and glucose (Table 2) which suggested I-6 (42.5%) and 1-3 (40%) linkages, fl-glucanes have been found in species of Penicillium [1], Eupenicillium [21 and Talaromyces [3,4], while in other species of the same genera an a (1-3) glucan was the main component of FI.…”
Section: Methylation Analysismentioning
confidence: 99%
See 2 more Smart Citations